Pulpal temperature rise during light-activated bleaching - (:unkn) unknown (My University, 2005)
The purpose of this study was to measure intrapulpal temperature rise induced by two kinds of bleaching gels when the tooth was exposed to a variety of light-curing units and a diode laser in vitro. The root portions of 80 extracted intact human maxillary central incisors were sectioned with a carborundum disk approximately 2 mm below the cementoenamel junction perpendicular to the long axis of the teeth. Two bleaching agents containing heat-enhancing colorant was applied to the labial surface. Light-curing units used were a conventional halogen (40 s), a high-intensity halogen (30 s), a light-emitting diode unit (40 s), and a diode laser (15 s). The temperature rise was measured in the pulpal chamber with a J-type thermocouple wire that was connected to a data logger. Ten specimens were used for each system and bleaching-agent combination. Differences between the starting temperature and highest temperature reading were taken and the calculated temperature changes were averaged to determine the mean value in temperature rise. Temperature rise values were compared using two-way analysis of variance (ANOVA) at a preset α of 0.05. Temperature rise varied significantly depending on curing unit and diode laser used. The diode laser induced significantly higher temperature increases than any other curing unit (11.7°C). The light-emitting diode unit produced the lowest temperature changes (6.0°C); however, there were no statistically significant differences among the curing units and there were no statistically significant differences between bleaching agents. Light activation of bleaching materials with diode laser caused higher temperature changes as compared to other curing units and the temperature rise detected was viewed as critical for pulpal health. © 2004 Wiley Periodicals, Inc.
Keywords: Dentin; Light-activated bleaching; Temperature